Penggunaan Cerita Jātaka untuk Peningkatan Kesadaran Berdana pada Siswa Sekolah Minggu Buddha (SMB) Pelita Dhamma di Vihara Buddhavamsa Lenek, Kabupaten Lombok Utara - Iswari, Nopia; Wardhani, Amita; Herman (STAB Kertarajasa, 2025)
This research aims to improve the donation practices among students of Pelita Dhamma Sunday School at Buddhavaṁsa Lenek Temple in North Lombok Regency through the use of Jataka Stories. It is a type of classroom action research consisting of three cycles involving four steps: planning, action, observation, and reflection. Data collection techniques include interviews, observations, documentation, and questionnaires. Based on pre-action interviews, the researcher found that understanding of Jataka stories and donation practices were lacking, and participants faced difficulties in responding.In the first cycle, there was an improvement in learning outcomes compared to pre-action, as participants were able to answer the researcher's questions. In the second cycle, there was further improvement, as participants not only answered questions but could also retell the stories. As for the third cycle, participants conducted a review by retelling all three Jataka stories taught. Regarding donation awareness, there was an increase after this learning process, as participants showed willingness to help both their parents and forgive their friends. Based on these improvement results, it can be concluded that the use of Jataka stories can enhance donation practices among students of Pelita Dhamma Sunday School at Buddhavaṁsa Lenek Temple in North Lombok Regency.